IMPLEMENTASI TQM UNTUK PENINGKATAN LABA PERUSAHAAN PADA PERUMDAM TIRTA KAHAYAN PALANGKA RAYA - Pamungkur Pamungkur; Sunarmie Sunarmie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Implementation of Total Quality Management (TQM) In Increaasing Company profits of Perumdam Tirta Kahayan Palangka Raya. This research was conducted using qualitative descriptive analysis method. the data analyzed is the result of data collection in Perumdam Tirta Kahayan Palangka Raya Perusahan Umum Daerah Air Minum (Perumdam) Kota Palangka Raya. Data in the form of financial statements, the data obtained in the form of writing in the form of a general description of, Perumdam Tirta Kahayan Palangka Raya namely collecting data through documentation interviews in the financial and accounting department of Perumdam Tirta Kahayan Palangka Raya. The research results obtained that Implementation of Total Quality Management (TQM) of Perumdam Tirta Kahayan Palangka Raya has been good applied, systematic in accordance with the principle of Total Quality Management (TQM) that is focus on customers, continuous system improvement, education and training, and employee involvement and empowerment. This Total Quality Management (TQM) also influences the increase in company profits of Perumdam Tirta Kahayan Palangka Raya.